Konsep Hukum dalam Pelaksanaan Peralihan Hak Atas Tanah Karena Jual Beli - Fathul Mujib Al-Mursyidi; Khusnul Yaqin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
It cannot be denied that in everyday people's lives there is still a lot of buying and selling of land that is done underhand. A land sale and purchase agreement that is not made before an Acting Land Deed Maker (PPAT) can cause losses to the buyer, for example the act of land sale and purchase in the case of Decision No. 34/Pdt.G/2020/PN.Dmk. The aim of this research is to answer the problem regarding the legal strength of land sale and purchase agreements that were not made before the Acting Land Deed Maker (PPAT) and to analyze the legal considerations of the Demak District Court judge's decision regarding No. 34/Pdt.G/2020/PN.Dmk. The results of this research show that 1) The legal strength of private deeds in sales and purchase agreements for land with ownership certificates in decision no. 34/Pdt.G/2020/PN.Dmk is valid and has legal force. This is proven by the positive arguments of the lawsuit, evidence and facts confirmed by the parties. 2) Analysis of the decision in case No. 34/Pdt.G/2020/PN.Dmk, the panel of judges gave permission to the Plaintiff to appear before the PPAT to sign the Deed of Sale and Purchase of land rights, granting the plaintiff's claim in part with verstek using the balance theory. The judge also carefully reviewed the contents of article 125 HIR, especially points 3 and 5, by deciding to grant the plaintiff's petitum not only based on the plaintiff's absence. The judge has also paid attention to the specifics of land sales and purchases regulated in the Basic Agrarian Law (UUPA). The authority to make certain authentic deeds, the difference is the legal basis that regulates the two. PPAT is Law Number 5 of 1960, Government Regulation Number 24 of 1997, Government Regulation Number 37 of 1998 and Regulation of the Head of the National Land Agency Number 1 of 2006, while Notary is Law Number 30 of 2004. However, in the provisions of Article 15 Paragraph (1) letter f of Law Number 30 of 2004 further strengthens the authority of Notaries in making deeds regarding land which are not deeds made by PPAT, especially deeds of land sale and purchase agreements.